NEW SPECTROPHOTOMETRIC DETERMINATION OF ESOMEPRAZOLE IN BULK AND PHARMACEUTICAL DOSAGE FORM USING WOOL FAST BLUE - Yoganda Swamy, MMV (Journal of Drug Delivery and Therapeutics, 2018)
The new, selective and sensitive visible spectrophotometric method has been developed for the estimation of Esomeprazole in bulk and in pharmaceutical preparations. This method is based on the reaction with wool fast blue, in the presence of buffer at PH 1.5 to form a colored species with a λmax 590nm.  Beer’s law is obeyed in the concentration range of 50-250µg/ml for both the methods.  The method was extended to pharmaceutical formulations and there was no interference form in any common pharmaceutical excipients and diluents. The result of analysis has been validated statistically and by recovery studies.  Keywords: Spectrophotometric determination Wool fast blue, Esomeprazole.